Primary Cutaneous Follicle Center Lymphoma Presenting as a Solitary Nodule on the Forearm of an Adolescent Girl: A Case Report and Literature Review - Al Harbi SM; Al Natour S; Al Saif NM; Al Saif N; Al Bayat MI (Dove Medical Press, 2023)
Sadan Mohammed Al Harbi,1 Sahar Al Natour,1 Nasser Mohammed Al Saif,1 Noura Al Saif,1 Methal Isam Al Bayat2 1Department of Dermatology, College of Medicine, Imam Abdulrahman Bin Faisal University, Dammam, Saudi Arabia; 2Department of Pathology, College of Medicine, Imam Abdulrahman Bin Faisal University, Dammam, Saudi ArabiaCorrespondence: Sadan Mohammed Al Harbi, Department of Dermatology, College of Medicine, Imam Abdulrahman Bin Faisal University, Post Box No. 1982, Dammam, 31441, Saudi Arabia, Email Smharbi@iau.edu.saAbstract: Primary cutaneous B-cell lymphomas (PCBCLs) are very rare to be seen in pediatric and adolescent age group, especially primary cutaneous follicle center lymphoma (PCFCL) which is considered the least occurring main subtype. Here, we describe a 16-year-old girl who developed a slowly growing solitary firm smooth surfaced erythematous nodule over her forearm. Histopathological examination showed a dense dermal nodular, periadnexal and perivascular lymphoid infiltrate extending deep to the subcutis. Immunohistochemical staining showed a B-cell population with positivity for CD20, variable staining for BCL6 and CD10 and uniquely staining for BCL2. Although a primary cutaneous marginal zone lymphoma (PCMZL) was considered but the presences of interfollicular BCL6 and CD10 positivity established the diagnosis of PCFCL. To our knowledge, only 12 cases of pediatric and adolescent PCFCL have been described in the literature.Keywords: B-cell lymphoma, skin cancer, pediatric, juvenile, lymphoproliferative disorder